Phylogeographic analyses of submesophotic snappers Etelis coruscans and Etelis "marshi" (family Lutjanidae) reveal concordant genetic structure across the Hawaiian Archipelago. - Kimberly R Andrews (Public Library of Science (PLoS), 2014)
The Hawaiian Archipelago has become a natural laboratory for understanding genetic connectivity in marine organisms as a result of the large number of population genetics studies that have been conducted across this island chain for a wide taxonomic range of organisms. However, population genetic studies have been conducted for only two species occurring in the mesophotic or submesophotic zones (30+m) in this archipelago. To gain a greater understanding of genetic connectivity in these deepwater habitats, we investigated the genetic structure of two submesophotic fish species (occurring ∼200-360 m) in this archipelago. We surveyed 16 locations across the archipelago for submesophotic snappers Etelis coruscans (N = 787) and E. "marshi" (formerly E. carbunculus; N = 770) with 436-490 bp of mtDNA cytochrome b and 10-11 microsatellite loci. Phylogeographic analyses reveal no geographic structuring of mtDNA lineages and recent coalescence times that are typical of shallow reef fauna. Population genetic analyses reveal no overall structure across most of the archipelago, a pattern also typical of dispersive shallow fishes. However some sites in the mid-archipelago (Raita Bank to French Frigate Shoals) had significant population differentiation. This pattern of no structure between ends of the Hawaiian range, and significant structure in the middle, was previously observed in a submesophotic snapper (Pristipomoides filamentosus) and a submesophotic grouper (Hyporthodus quernus). Three of these four species also have elevated genetic diversity in the mid-archipelago. Biophysical larval dispersal models from previous studies indicate that this elevated diversity may result from larval supplement from Johnston Atoll, ∼800 km southwest of Hawaii. In this case the boundaries of stocks for fishery management cannot be defined simply in terms of geography, and fishery management in Hawaii may need to incorporate external larval supply into management plans.